Interaction of erythrocyte membranes with derivatives of 3-oxypiridines - E. E. Kuznetsova (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
In connection with the increased interest in the use of auto-erythrocytes for directional drug transport, the study of the ability of erythrocytes to sorb an antioxidant drug is becoming topical. The article considers the method of spectrophotometry developed for evaluating the ability of erythrocytes to load with a mexidol preparation under conditions of natural sorption and a method created for determining the drug concentration in erythrocyte biological medias. Materials and methods. The peripheral blood of 15 clinically healthy males aged 20 to 45 years was used as an object of the study. A pharmaceutical preparation of oxymethylethylpyridine succinate-mexidol (ZAO «Pharmasoft», Russia) was used for clinical studies. The drug belongs to the group of 3-hydroxypyridines. The inclusion of mexidol was carried out by direct incubation of erythrocytes in a medium containing this preparation. The concentrations of the preparation were 1.25,2.5 and 5 ßg/ml and the incubation time was 15,20 and 3o minutes. The supernatant was obtained by centrifugation for 10 minutes at 3000 rpm on a SF-2000 spectrophotometer at a wavelength of 630 nm. In addition to the pharmacopoeial method, the oxidation-reduction reaction of the supernatant with methylene blue was used. Results. When measuring the spectra of the supernatant with different concentration of the preparation and using methylene blue, a regression relationship between mexidol and optical density was established, and the optimal exposure time of red blood cells and the drug was determined. These data can be used to control the directional transport of the drug to target organs. A model of the equation for determination of the mexidol content in biomedids is proposed.